2009
DOI: 10.1111/j.1365-2427.2008.02119.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual patterns of phytoplankton density and primary production in a large, shallow lake: the central role of light

Abstract: 1. We studied the seasonal dynamics of suspended particulate matter in a turbid, large shallow lake during an annual period . We relate the patterns of seston concentration (total suspended solids), phytoplankton biomass and water transparency to the seasonal pattern of incident solar radiation (I 0 ). We also report the seasonal trends of phytoplankton primary production (PP) and photosynthesis photoinhibition due to photosynthetically active radiation (PAR) and ultraviolet radiation (UVR) (I b and UV 50 ). 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 47 publications
(72 reference statements)
5
49
0
8
Order By: Relevance
“…Solar insolation and precipitation are two factors that influence these processes, along with water column light penetration and heat absorbance (Cloern 1991;Torremorell et al 2009). To describe ecological succession of the Estuary's food web taxa, we calculated monthly mean solar declination for San Francisco Bay using the NOAA solar calculator (http:// www.esrl.noaa.gov/gmd/grad/solcalc/).…”
Section: Annual Ecological Successionmentioning
confidence: 99%
“…Solar insolation and precipitation are two factors that influence these processes, along with water column light penetration and heat absorbance (Cloern 1991;Torremorell et al 2009). To describe ecological succession of the Estuary's food web taxa, we calculated monthly mean solar declination for San Francisco Bay using the NOAA solar calculator (http:// www.esrl.noaa.gov/gmd/grad/solcalc/).…”
Section: Annual Ecological Successionmentioning
confidence: 99%
“…Moreover, through this method, Colautti et al (2010) obtained the best mean daily growth rate of 0.86mm day -1 ever recorded for juveniles of 45-60 days of age, and survival rates between 59-65%, which are within the range registered by intensive and semi-intensive culture practices. Nevertheless, those authors pointed out that during the months of autumn and winter, when the productivity of these lakes decreases (Torremorell et al, 2009), pejerrey growth in extensive cage culture becomes limited by low temperatures and by the zooplankton availability. As extension of this findings, Colautti et al (2010) suggested that those rates could be improved by supplying artificial food during the periods when the lakes productivity diminish.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of darkacclimated algae may show increased sensitivity to variations in incidental irradiance than do light-acclimated algal communities (O'Brien et al 2009). We suggest that direct measurements of the irradiance intensity, the site-specific algal growth rate, and quantitative assessments of the relationship between photosynthesis and irradiance (P-I) are needed to develop a better understanding of how light availability alters the temporal dynamics of algal biomass and to examine the combined effects of light and nutrients on the growth of epilithic algae in streams (Kaiblinger et al 2007;Torremorell et al 2009). …”
Section: Effects Of Light Availabilitymentioning
confidence: 99%